Resources Management, Utilization & Optimization in the Light of The Holy Quran (A Study to Reveal Qur’anic Guidance on Resource Management and Utilization) - Zafar Iqbal; Dr. Sana Ullah Hussain (Al Manhal Research Journal, 2025)
The existence and survival of mankind is dependent on various material resources. These resources fulfill the human requirements ranging from basic needs e.g. water, shelter and food to endless wishes and luxuries of life. Therefore, the importance and necessity of resources in today’s modern world is much more than older ages. Consequently, the quantum of researches on resources and its management has also increased manifold. In the same context, we find numerous discussions in Quran, which are hinted towards various aspects of Resources and Resource Management. Quran is the last book revealed for guidance of human beings for all times to come. There is no doubt that Quran is basically a book of Hidayat (divine guidance) however, it also provides guidance in other fields of human needs. The Almighty Allah has purposefully illustrated various examples and explained related phenomenon in everyday life to open the eyes and ears of the human beings. It is because providing divine guidance that Allah Almighty has enlightened Hidayat (guidance) in so many different ways that every human can gain guidance as per his own personal mindset. Due to this reason, we see discussions in Quran which are related to Tauheed (Singularity of Allah), Risalat (Prophet hood), Qayamah (Day of Judgment), good and bad deeds, Heaven and Hell and on lot many other topics. One of the topics widely discussed in the Quran is related to Resources. This is due to the fact that human life and its sustenance against various odds is dependent on availability and adequacy of various resources. This includes both material and non-material resources. Quran being a divine guidance addresses both requirements of human needs. The material resources include water, air, food, shelter, sun light, iron and various other materials. Quran not only mentions and discusses material resources but also highlights and indicates their utilization and optimization in their management.